Vanadium oxide modified bismuth tin alloy electrocatalyst and preparation method and application thereof
By modifying vanadium oxide clusters on the surface of bismuth tin alloy nanosheets, the highly active electrocatalyst BiSn(VOx) was constructed, and the problems of low selectivity and limited production efficiency of carbon dioxide reduction formate in the prior art were solved, thereby achieving efficient and stable electrocatalytic reactions.
Patent Information
- Application Number
- CN202411840130.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing electrochemical carbon dioxide reduction technology formate production has problems of low selectivity and limited production efficiency.
The highly active electrocatalyst BiSn(VOx) was constructed by modifying the vanadium oxide clusters on the surface of bismuth tin alloy nanosheets with abundant active sites.
It has achieved high selectivity, high activity and good stability in electrocatalytic carbon dioxide reduction reaction, and has important application value in energy storage and carbon dioxide resource utilization.
Smart Images

Figure CN119776887A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanomaterials and electrocatalysis, and in particular to an electrocatalyst of a bismuth-tin alloy modified with vanadium oxide, and a preparation method and application thereof. Background Art
[0002] With the development of science and technology, the consumption of fossil fuels has increased dramatically, leading to an increase in the concentration of carbon dioxide in the atmosphere. The electrochemical carbon dioxide reduction reaction (CO2RR) converts carbon dioxide into value-added chemicals or fuels, which is a promising strategy to alleviate the excessive burning of fossil fuels and the greenhouse effect. In aqueous solution, carbon dioxide electrochemical reduction can be converted into a variety of products, among which formate, as a low-toxic and energy-intensive electrochemical carbon dioxide reduction product, has broad application prospects in energy and industrial related fields. However, the electrochemical carbon dioxide reduction to formate has bottlenecks such as low selectivity and limited production efficiency, and there is also a competitive reaction for hydrogen evolution. Therefore, the development of efficient catalysts with high activity, high selectivity and long-term stability is crucial for the practical application of formate on a large scale. Summary of the invention
[0003] 1. Technical issues to be solved
[0004] In view of the shortcomings of the prior art, the present invention provides a vanadium oxide-modified bismuth-tin alloy electrocatalyst and its preparation method and application. By modifying the surface of bismuth-tin alloy nanosheets with abundant active sites with vanadium oxide clusters, a highly active electrocatalyst is constructed to solve the problems raised in the above-mentioned background technology.
[0005] (II) Technical solution
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0007] According to a first aspect of the present invention, a vanadium oxide modified bismuth-tin alloy electrocatalyst is provided, wherein the electrocatalyst is BiSn(VO x ), having a two-dimensional nanosheet morphology, wherein the BiSn is an alloy, VO x The BiSn nanosheets are modified in the form of clusters, and BiSn(VO x ) The lattice spacing corresponds to the (012) plane of Bi.
[0008] Preferably, the electrocatalyst is in a nanosheet structure, and the size of the nanosheet is 200 to 500 nm.
[0009] According to a second aspect of the present invention, there is provided a method for preparing a vanadium oxide modified bismuth-tin alloy electrocatalyst, comprising the following steps:
[0010] (1) dissolving bismuth nitrate, tin chloride and ammonium metavanadate in a hydrochloric acid solution and stirring uniformly to obtain an electrolyte;
[0011] (2) using the electrolyte of step (1) to construct an electrolytic cell with a three-electrode system, using carbon cloth as a working electrode, a saturated Ag / AgCl electrode as a reference electrode, and a platinum sheet as a counter electrode, applying a constant current density for electrochemical deposition to obtain an electrocatalyst;
[0012] (3) Washing the electrocatalyst alternately with water and ethanol and drying in vacuo to obtain the vanadium oxide-modified bismuth-tin electrocatalyst.
[0013] Preferably, in step (1), the molar ratio of tin chloride, bismuth nitrate and ammonium metavanadate is 1:11-12:3-6;
[0014] The concentration of the hydrochloric acid solution is 0.1-1 M, and the amount of the hydrochloric acid solution added is 50 mL.
[0015] Further preferably, the molar ratio of tin chloride, bismuth nitrate and ammonium metavanadate is 1:11:4;
[0016] The concentration of the hydrochloric acid solution is 0.5M.
[0017] Preferably, in step (2), during the electrochemical deposition process, the constant current density is -5 to -50 mA / cm 2 , the electrochemical deposition time is 200 to 600 s.
[0018] Further preferably, in step (2), during the electrochemical deposition process, the constant current density is -25 mA / cm 2 , the electrochemical deposition time is 400s.
[0019] Preferably, in step (3), the electrocatalyst is washed alternately with water and ethanol 3 to 5 times;
[0020] The vacuum drying temperature is 60-80° C., and the vacuum drying time is 6-8 hours.
[0021] According to a third aspect of the present invention, there is provided a vanadium oxide modified bismuth-tin alloy electrocatalyst or a vanadium oxide modified bismuth-tin alloy electrocatalyst obtained according to the above preparation method and its use in a carbon dioxide electroreduction reaction.
[0022] Preferably, in a flow-type electrolytic cell, the vanadium oxide-modified bismuth-tin alloy electrocatalyst maintains a Faraday efficiency (FE) of formate above 90% in the potential range of -0.5 to -1.3 V (vs. RHE).
[0023] According to a fourth aspect of the present invention, there is provided a vanadium oxide modified bismuth-tin alloy electrocatalyst or a vanadium oxide modified bismuth-tin alloy electrocatalyst obtained according to the above preparation method and its use in a reversible zinc-carbon dioxide battery.
[0024] Preferably, the vanadium oxide modified bismuth-tin alloy electrocatalyst is used as the cathode and the zinc foil is used as the anode. The battery is tested under specific electrolyte conditions. Specifically, the cathode electrolyte is 0.5M potassium bicarbonate and the anode electrolyte is a mixture of 6M potassium hydroxide and 0.2M zinc acetate. The maximum power density of the battery can reach 3.8mW / cm 2 .
[0025] According to a fifth aspect of the present invention, there is provided a vanadium oxide modified bismuth-tin alloy electrocatalyst or a vanadium oxide modified bismuth-tin alloy electrocatalyst obtained according to the above preparation method for use in a carbon dioxide reduction reaction system assisted by an ethylene glycol oxidation reaction.
[0026] Preferably, BiSn(VO x )||NiCoLDH electrode combination, the Faradaic efficiency of formate can reach 182% at 0.6V.
[0027] (III) Beneficial effects
[0028] The present invention provides a vanadium oxide modified bismuth-tin alloy electrocatalyst and its preparation method and application. It has the following beneficial effects:
[0029] (1) This scheme provides a vanadium oxide modified bismuth-tin alloy electrocatalyst. The introduction of tin alloy can promote the adsorption and activation of carbon dioxide molecules, and the surface-modified vanadium oxide (VO x ) can accelerate water dissociation, thereby providing sufficient hydrogen protons (H*) supply, thereby improving the subsequent formation of *OCHO species. Based on this, the catalyst has high selectivity, high activity and good stability in the electrocatalytic carbon dioxide reduction reaction.
[0030] (2) The present invention provides a method for preparing a vanadium oxide-modified bismuth-tin alloy electrocatalyst, which can be synthesized by a one-step deposition method, is easy to mass produce, improves production efficiency, and is environmentally friendly.
[0031] (3) The vanadium oxide-modified bismuth-tin alloy electrocatalyst provided in this scheme exhibits excellent performance in the process of carbon dioxide electroreduction to formate, and has important application value in energy storage and carbon dioxide resource utilization. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A schematic diagram of the synthesis of a vanadium oxide-modified bismuth-tin alloy electrocatalyst of the present invention;
[0033] Figure 2 The electrocatalyst BiSn(VO x )’s X-ray diffraction pattern;
[0034] Figure 3 The electrocatalyst BiSn(VO x ), where (a) is a TEM image and (b) is a HRTEM image;
[0035] Figure 4 The electrocatalyst BiSn(VO x ) XPS spectra before and after argon ion etching, where (a) Bi 4fXPS spectrum, (b) Sn 3dXPS spectrum, and (c) V2p XPS spectrum;
[0036] Figure 5 The electrocatalyst BiSn(VO x ) LSV curves obtained by flow cell testing in CO2 and Ar saturated electrolytes;
[0037] Figure 6 The electrocatalyst BiSn(VO x ) Faradaic efficiency diagram of H2, CO, and formate products in the flow cell;
[0038] Figure 7 The electrocatalyst BiSn(VO x ) Stability test diagram in flow cell;
[0039] Figure 8 The electrocatalyst BiSn(VO x ) discharge polarization curve and power density curve in Zn-CO2 battery;
[0040] Fig. 9 The electrocatalyst BiSn(VO x ) LSV curve in the carbon dioxide reduction reaction system assisted by ethylene glycol oxidation reaction;
[0041] Fig.10 The electrocatalyst BiSn(VO x ) Faradaic efficiency of formate at different voltages in a CO2 reduction reaction system assisted by ethylene glycol oxidation;
[0042] Fig.11 It is a comparison diagram of the LSV curves of the electrocatalysts prepared in Comparative Example 1, Comparative Example 2 and Example 1 of the present invention. DETAILED DESCRIPTION
[0043] In order to better illustrate the content of the present invention, a detailed description is given below in conjunction with specific embodiments.
[0044] Example 1
[0045] A method for preparing a vanadium oxide modified bismuth-tin alloy electrocatalyst, such as Figure 1 As shown, the following steps are included:
[0046] Step 1, accurately weigh 55mmol Bi(NO3)3·5H2O, 5mmol SnCl4·5H2O and 20mmol NH4VO3, dissolve them in 50ml 0.5M HCl solution, stir for 20 minutes until the solution is uniform, and obtain an electrolyte;
[0047] Step 2: Take a carbon cloth with an area of 1 cm × 2 cm as the working electrode, a saturated Ag / AgCl electrode as the reference electrode, and a platinum sheet as the counter electrode. Use a constant current density of -25 mA / cm 2 The electrodeposition method was used to deposit BiSn(VO x ) electrocatalyst;
[0048] Step three, washing the prepared electrocatalyst with water and ethanol alternately for three times, and then drying it in a vacuum oven at 60° C. for 6 hours to obtain a vanadium oxide-modified bismuth-tin alloy electrocatalyst.
[0049] Example 2
[0050] Step 1, accurately weigh 55 mmol of Bi(NO3)3·5H2O, 4 mmol of SnCl4·5H2O and 20 mmol of NH4VO3, dissolve them in 50 ml of 0.5 M HCl solution, and stir for 20 minutes until the solution is uniform to obtain an electrolyte;
[0051] Step 2: Take a carbon cloth with an area of 1 cm × 2 cm as the working electrode, a saturated Ag / AgCl electrode as the reference electrode, and a platinum sheet as the counter electrode. Use a constant current density of -25 mA / cm 2 The electrodeposition method was used to deposit BiSn(VO x ) electrocatalyst;
[0052] Step three, washing the prepared electrocatalyst with water and ethanol alternately for three times, and then drying it in a vacuum oven at 60° C. for 6 hours to obtain a vanadium oxide-modified bismuth-tin alloy electrocatalyst.
[0053] Example 3
[0054] Step 1, accurately weigh 55mmol Bi(NO3)3·5H2O, 6mmol SnCl4·5H2O and 20mmol NH4VO3, dissolve them in 50ml 0.5M HCl solution, stir for 20 minutes until the solution is uniform, and obtain an electrolyte;
[0055] Step 2: Take a carbon cloth with an area of 1 cm × 2 cm as the working electrode, a saturated Ag / AgCl electrode as the reference electrode, and a platinum sheet as the counter electrode. Use a constant current density of -25 mA / cm 2 The electrodeposition method was used to deposit BiSn(VO x ) electrocatalyst;
[0056] Step three, washing the prepared electrocatalyst with water and ethanol alternately for three times, and then drying it in a vacuum oven at 60° C. for 6 hours to obtain a vanadium oxide-modified bismuth-tin alloy electrocatalyst.
[0057] Example 4
[0058] Step 1, accurately weigh 55 mmol of Bi(NO3)3·5H2O, 5 mmol of SnCl4·5H2O and 15 mmol of NH4VO3, dissolve them in 50 ml of 0.5 M HCl solution, and stir for 20 minutes until the solution is uniform to obtain an electrolyte;
[0059] Step 2: Take a carbon cloth with an area of 1 cm × 2 cm as the working electrode, a saturated Ag / AgCl electrode as the reference electrode, and a platinum sheet as the counter electrode. Use a constant current density of -25 mA / cm 2 The electrodeposition method was used to deposit BiSn(VO x ) electrocatalyst;
[0060] Step three, washing the prepared electrocatalyst with water and ethanol alternately for three times, and then drying it in a vacuum oven at 60° C. for 6 hours to obtain a vanadium oxide-modified bismuth-tin alloy electrocatalyst.
[0061] Example 5
[0062] Step 1, accurately weigh 55 mmol of Bi(NO3)3·5H2O, 5 mmol of SnCl4·5H2O and 30 mmol of NH4VO3, dissolve them in 50 ml of 0.5 M HCl solution, and stir for 20 minutes until the solution is uniform to obtain an electrolyte;
[0063] Step 2: Take a carbon cloth with an area of 1 cm × 2 cm as the working electrode, a saturated Ag / AgCl electrode as the reference electrode, and a platinum sheet as the counter electrode. Use a constant current density of -25 mA / cm2 The electrodeposition method was used to deposit BiSn(VO x ) electrocatalyst;
[0064] Step three, washing the prepared electrocatalyst with water and ethanol alternately for three times, and then drying it in a vacuum oven at 60° C. for 6 hours to obtain a vanadium oxide-modified bismuth-tin alloy electrocatalyst.
[0065] Example 6
[0066] Step 1, accurately weigh 55 mmol of Bi(NO3)3·5H2O, 5 mmol of SnCl4·5H2O and 20 mmol of NH4VO3, dissolve them in 50 ml of 0.1 M HCl solution, and stir for 20 minutes until the solution is uniform to obtain an electrolyte;
[0067] Step 2: Take a carbon cloth with an area of 1 cm × 2 cm as the working electrode, a saturated Ag / AgCl electrode as the reference electrode, and a platinum sheet as the counter electrode. Use a constant current density of -25 mA / cm 2 The electrodeposition method was used to deposit BiSn(VO x ) electrocatalyst;
[0068] Step three, washing the prepared electrocatalyst with water and ethanol alternately for three times, and then drying it in a vacuum oven at 60° C. for 6 hours to obtain a vanadium oxide-modified bismuth-tin alloy electrocatalyst.
[0069] Example 7
[0070] Step 1, accurately weigh 55 mmol of Bi(NO3)3·5H2O, 5 mmol of SnCl4·5H2O and 20 mmol of NH4VO3, dissolve them in 50 ml of 1.0 M HCl solution, and stir for 20 minutes until the solution is uniform to obtain an electrolyte;
[0071] Step 2: Take a carbon cloth with an area of 1 cm × 2 cm as the working electrode, a saturated Ag / AgCl electrode as the reference electrode, and a platinum sheet as the counter electrode. Use a constant current density of -25 mA / cm 2 The electrodeposition method was used to deposit BiSn(VO x ) electrocatalyst;
[0072] Step three, washing the prepared electrocatalyst with water and ethanol alternately for three times, and then drying it in a vacuum oven at 60° C. for 6 hours to obtain a vanadium oxide-modified bismuth-tin alloy electrocatalyst.
[0073] Example 8
[0074] Step 1, accurately weigh 55 mmol of Bi(NO3)3·5H2O, 5 mmol of SnCl4·5H2O and 20 mmol of NH4VO3, dissolve them in 50 ml of 0.5 M HCl solution, and stir for 20 minutes until the solution is uniform to obtain an electrolyte;
[0075] Step 2: Take a carbon cloth with an area of 1 cm × 2 cm as the working electrode, a saturated Ag / AgCl electrode as the reference electrode, and a platinum sheet as the counter electrode. Use a constant current density of -50 mA / cm 2 The electrodeposition method was used to deposit BiSn(VO x ) electrocatalyst;
[0076] Step three, washing the prepared electrocatalyst with water and ethanol alternately for three times, and then drying it in a vacuum oven at 60° C. for 6 hours to obtain a vanadium oxide-modified bismuth-tin alloy electrocatalyst.
[0077] Example 9
[0078] Step 1, accurately weigh 55 mmol of Bi(NO3)3·5H2O, 5 mmol of SnCl4·5H2O and 20 mmol of NH4VO3, dissolve them in 50 ml of 0.5 M HCl solution, and stir for 20 minutes until the solution is uniform to obtain an electrolyte;
[0079] Step 2: Take a carbon cloth with an area of 1 cm × 2 cm as the working electrode, a saturated Ag / AgCl electrode as the reference electrode, and a platinum sheet as the counter electrode. Use a constant current density of -5 mA / cm 2 The electrodeposition method was used to deposit BiSn(VO x ) electrocatalyst;
[0080] Step three, washing the prepared electrocatalyst with water and ethanol alternately for three times, and then drying it in a vacuum oven at 60° C. for 6 hours to obtain a vanadium oxide-modified bismuth-tin alloy electrocatalyst.
[0081] Example 10
[0082] Step 1, accurately weigh 55 mmol of Bi(NO3)3·5H2O, 5 mmol of SnCl4·5H2O and 20 mmol of NH4VO3, dissolve them in 50 ml of 0.5 M HCl solution, and stir for 20 minutes until the solution is uniform to obtain an electrolyte;
[0083] Step 2: Take a carbon cloth with an area of 1 cm × 2 cm as the working electrode, a saturated Ag / AgCl electrode as the reference electrode, and a platinum sheet as the counter electrode. Use a constant current density of -25 mA / cm2 The electrodeposition method was used to deposit BiSn(VO x ) electrocatalyst;
[0084] Step three, washing the prepared electrocatalyst with water and ethanol alternately for three times, and then drying it in a vacuum oven at 60° C. for 6 hours to obtain a vanadium oxide-modified bismuth-tin alloy electrocatalyst.
[0085] Embodiment 11
[0086] Step 1, accurately weigh 55 mmol of Bi(NO3)3·5H2O, 5 mmol of SnCl4·5H2O and 20 mmol of NH4VO3, dissolve them in 50 ml of 0.5 M HCl solution, and stir for 20 minutes until the solution is uniform to obtain an electrolyte;
[0087] Step 2: Take a carbon cloth with an area of 1 cm × 2 cm as the working electrode, a saturated Ag / AgCl electrode as the reference electrode, and a platinum sheet as the counter electrode. Use a constant current density of -25 mA / cm 2 The electrodeposition method was used to deposit BiSn(VO x ) electrocatalyst;
[0088] Step three, washing the prepared electrocatalyst with water and ethanol alternately for three times, and then drying it in a vacuum oven at 60° C. for 6 hours to obtain a vanadium oxide-modified bismuth-tin alloy electrocatalyst.
[0089] Comparative Example 1
[0090] A method for preparing a metallic bismuth catalyst (Bi), comprising the following steps:
[0091] Step 1, accurately weigh 55 mmol of Bi(NO3)3·5H2O and dissolve it in 50 ml of 0.5 M HCl solution, and stir for 20 minutes until the solution is uniform to obtain an electrolyte;
[0092] Step 2: Take a carbon cloth with an area of 1 cm × 2 cm as the working electrode, a saturated Ag / AgCl electrode as the reference electrode, and a platinum sheet as the counter electrode. Use a constant current density of -25 mA / cm 2 Electrodeposition was carried out in the above electrolyte for 400 seconds to obtain metallic Bi;
[0093] Step three, the prepared metal Bi was washed alternately with water and ethanol for three times, and then dried in a vacuum oven at 60° C. for 6 h to obtain a metal Bi electrocatalyst.
[0094] Comparative Example 2
[0095] A method for preparing a bismuth-tin alloy catalyst (BiSn) comprises the following steps:
[0096] Step 1, accurately weigh 55 mmol of Bi(NO3)3·5H2O and 5 mmol of SnCl4·5H2O and dissolve them in 50 ml of 0.5 M HCl solution, and stir for 20 minutes until the solution is uniform to obtain an electrolyte;
[0097] Step 2: Take a carbon cloth with an area of 1 cm × 2 cm as the working electrode, a saturated Ag / AgCl electrode as the reference electrode, and a platinum sheet as the counter electrode. Use a constant current density of -25 mA / cm 2 The BiSn alloy was deposited in the above electrolyte for 400 seconds by electrodeposition method.
[0098] Step three, washing the prepared BiSn alloy with water and ethanol alternately for three times, and then drying it in a vacuum oven at 60° C. for 6 h to obtain a BiSn alloy catalytic electrode.
[0099] Performance Testing
[0100] The BiSn(VO prepared in Example 1 x ) Electrocatalysts were subjected to XRD analysis, such as Figure 2 As shown, the X-ray diffraction pattern shows that the synthesized BiSn(VO x ) The electrocatalyst phase is still single-element Bi, corresponding to the standard spectrum of Bi JCPDS#85-1329.
[0101] The BiSn(VO prepared in Example 1 x ) Electrocatalysts were subjected to TEM analysis, such as Figure 3 As shown, according to Figure 3 From Figure a and Figure b, we can see that BiSn(VO x ) materials present nanosheet morphology, BiSn(VO x ) corresponds to the (012) plane of Bi.
[0102] The BiSn(VO prepared in Example 1 x ) Electrocatalysts were subjected to X-ray photoelectron spectroscopy analysis, such as Figure 4 As shown in the figure, the changes before and after argon ion etching confirm that BiSn(VO x ) In the electrocatalyst, bismuth and tin exist in the form of alloys, while vanadium exists in the form of vanadium oxide, constituting a bismuth-tin alloy material modified with vanadium oxide.
[0103] The BiSn(VO prepared in Example 1 x ) The performance of the electrocatalyst was tested in a flow-type electrolytic cell, such as Figure 5As shown, the electrolytes are 1M potassium hydroxide solutions saturated with CO2 and saturated with Ar, respectively. x ) catalyst has a larger current density in CO2-saturated electrolyte, demonstrating the intrinsic high CO2 reduction performance of this material.
[0104] The BiSn(VO prepared in Example 1 x ) The performance of the electrocatalyst was tested in a flow-type electrolytic cell, such as Figure 6 As shown in the figure, in the potential range of -0.5V to -1.3V (vs.RHE), the formate Faraday efficiency shows a trend of first increasing and then decreasing. At a potential of -0.6V vs.RHE, the highest formate Faraday efficiency can reach 98%, and the formate Faraday efficiency is always maintained above 90%, which proves that the prepared BiSn(VO x )The electrocatalyst has high selectivity for formate.
[0105] In order to evaluate the BiSn(VO x ) Long-term cycling test stability of electrocatalysts and their ability to continuously produce formate, Figure 7 The BiSn(VO prepared in Example 1 x ) electrocatalyst in 1M potassium hydroxide electrolyte, using a flow cell, electrolyzed for 100 h at a constant potential of -0.6 V vs. RHE. The test results show that the BiSn(VO x )Electrocatalysts have excellent stability and great market application prospects.
[0106] Figure 8 The BiSn(VO x ) Performance of electrocatalyst in rechargeable Zn-CO2 battery. The assembled Zn-CO2 battery has excellent rechargeable and dischargeable performance, and at 4mA / cm 2 The peak power can reach 3.8mW / cm 2 .
[0107] Fig. 9 The NiCo LDH sample was used as the anode catalyst and the BiSn(VO x ) electrocatalyst as the cathode to form a co-electrolysis system, wherein the cathode electrolyte is 1M potassium hydroxide and the anolyte is 1M potassium hydroxide + 1M ethylene glycol. The results confirm that the electrolytic cell constructed using ethylene glycol oxidation reaction as the anode has a higher current density.
[0108] Fig.10The NiCo LDH sample was used as the anode catalyst and the BiSn(VO x ) catalyst as the cathode to form a co-electrolysis system. The results showed that the total Faraday efficiency of formate in the electrolytic cell could reach 182% at a voltage of 0.6V.
[0109] Fig.11 This is a performance comparison chart of the polarization curves obtained for BiSn(VOx) and BiSn and Bi catalysts prepared in the comparative example in a flow-type electrolytic cell. The results confirm that Sn alloying treatment helps to improve the electrocatalytic CO2 reduction performance of Bi materials, while the surface modification of VOx clusters can further improve the performance of BiSn materials, thereby achieving performance optimization.
[0110] According to the above performance tests, the vanadium oxide-modified bismuth-tin alloy electrocatalyst provided by the present invention, and its preparation method and application, the vanadium oxide-modified bismuth-tin alloy electrocatalyst prepared by the synthesis method provided by the present invention has a nanosheet structure, good crystallinity and stability, and is applied to the electrocatalytic reduction of carbon dioxide to formate. It shows high activity and excellent stability. In a wide potential window, the catalyst can achieve a formate Faraday efficiency of more than 90%, and shows good stability in the cycle test. In addition, the electrocatalyst exhibits high power density in a rechargeable Zn-CO2 battery system and has excellent co-electrolysis performance, proving its potential application value in energy storage and conversion.
[0111] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A vanadium oxide modified bismuth-tin alloy electrocatalyst, characterized in that: The electrocatalyst is BiSn(VO x ), having a two-dimensional nanosheet morphology, wherein the BiSn is an alloy, VO x The BiSn nanosheets are modified in the form of clusters, and BiSn(VO x ) The lattice spacing corresponds to the (012) plane of Bi.
2. The vanadium oxide modified bismuth-tin alloy electrocatalyst according to claim 1, characterized in that: The electrocatalyst is in a nanosheet structure, and the size of the nanosheet is 200-500nm.
3. A method for preparing a vanadium oxide modified bismuth-tin alloy electrocatalyst according to claim 1 or 2, characterized in that: The following steps are involved: (1) dissolving bismuth nitrate, tin chloride and ammonium metavanadate in a hydrochloric acid solution and stirring uniformly to obtain an electrolyte; (2) using the electrolyte of step (1) to construct an electrolytic cell with a three-electrode system, using carbon cloth as a working electrode, a saturated Ag / AgCl electrode as a reference electrode, and a platinum sheet as a counter electrode, applying a constant current density for electrochemical deposition to obtain an electrocatalyst; (3) Washing the electrocatalyst with water and ethanol alternately and drying in vacuo to obtain the vanadium oxide-modified bismuth-tin alloy electrocatalyst.
4. The method for preparing a vanadium oxide modified bismuth-tin alloy electrocatalyst according to claim 3, characterized in that: In step (1), the molar ratio of tin chloride, bismuth nitrate and ammonium metavanadate is 1:11-12:3-6; The concentration of the hydrochloric acid solution is 0.1-1 M, and the amount of the hydrochloric acid solution added is 50 mL.
5. The method for preparing a vanadium oxide modified bismuth-tin alloy electrocatalyst according to claim 3, characterized in that: In step (2), during the electrochemical deposition process, the constant current density is -5 to -50 mA / cm 2 , the electrochemical deposition time is 200 to 600 s.
6. The method for preparing a vanadium oxide modified bismuth-tin alloy electrocatalyst according to claim 3, characterized in that: In step (3), the electrocatalyst is washed alternately with water and ethanol 3 to 5 times; The vacuum drying temperature is 60-80° C., and the vacuum drying time is 6-8 hours.
7. Use of a vanadium oxide modified bismuth-tin alloy electrocatalyst as claimed in claim 1 or 2 or a vanadium oxide modified bismuth-tin alloy electrocatalyst obtained by the preparation method according to any one of claims 3 to 6 in carbon dioxide electroreduction reaction.
8. Use of a vanadium oxide-modified bismuth-tin alloy electrocatalyst according to claim 1 or 2 or a vanadium oxide-modified bismuth-tin alloy electrocatalyst obtained by the preparation method according to any one of claims 3 to 6 in a reversible zinc-carbon dioxide battery.
9. Use of a vanadium oxide modified bismuth-tin alloy electrocatalyst as claimed in claim 1 or 2 or a vanadium oxide modified bismuth-tin alloy electrocatalyst obtained by the preparation method according to any one of claims 3 to 6 in a carbon dioxide reduction reaction system assisted by ethylene glycol oxidation reaction.
Citation Information
Patent Citations
Pucherite-stannic oxide complex photocatalyst as well as preparation method and application thereof
CN105032399A
Alkaline solution hydrogen evolution electrocatalyst V2O3-NiPt and preparation method and application thereof
CN110064406A
Preparation method of ultrathin two-dimensional vanadium-phosphorus-oxygen composite metal oxide nanosheet crystals
CN111204728A
Distance recommendation device for providing recommendation distance at third location
KR102579222B1
Catalysts or catalytic systems comprising liquid metals and uses thereof
WO2021077164A1
Cited By
Bismuth-modified wrinkled two-dimensional tin oxide composite material as well as preparation method and application thereof
CN122147432A